Young Lives Preliminary Country Report: Peru - Escobal, J; Lanata, C; Madrid, S; Penny, M; Saavedra, J; Suárez, P; Verastegui, H; Villar, E; Huttly, S (2003)
This report presents a brief literature review of childhood poverty in Peru, identifies key national audiences for the Young Lives study, explains the study methods used and presents provisional evidence, conclusions and policy implications. The Peruvian economy underwent a series of crises and external shocks in the 1980s and 1990s. The number of poor households rose rapidly from 43 per cent of the total in 1985-86 to 59 per cent in 1991. Despite reforms in the 1990s, Peru has one of the highest rates of income inequality in Latin America. Childhood poverty rates are higher than poverty rates in the general population. Health indicators reveal a large gap between rural and urban regions. Peru has the third highest child malnutrition rate in Latin America and the third worst ranking for nutritional inequality. In education, by contrast, the Peruvian government has made great strides. By 2000, primary school enrolment had almost become universal and around 73 per cent of 12- to 16-year-olds were enrolled in secondary education. There are no accurate statistics but it is also estimated that over two million children work in Peru. Among 14- to 17-year-olds that work, 40 per cent are out of school. Working children who are in school are, on average, two to four years behind their peers. Peru’s Children and Adolescents Code, passed in 2000, brought national legislation into line with the standards of the Convention on the Rights of the Child. However, state agencies in charge of providing protection and services, are under-resourced. Young Lives research is providing a unique opportunity to identify how government policies and programmes could improve children’s lives. Young Lives research in Peru provides a unique opportunity to learn about poverty in the country and to contribute to the formulation of effective policies aimed at improving children’s lives. The preliminary results presented in this paper provide important data on housing, nutrition, food aid, health, education, the environment, economic shocks, and child labour. The authors outline conclusions and implications for pro-poor pro-child policy based on this data.